Results of Carotid Endarterectomy Performed at Different Times During the Acute Period of Ischemic Stroke - A. D. Pryamikov; R. Yu. Loluev; S. A. Asratyan; A. B. Mironkov; A. I. Khripun (Неотложная медицинская помощь, 2024)
AIM OF STUDY. To compare the results of carotid endarterectomy performed at different times (1st, 2nd and 3rd week) of the acute period of ischemic stroke.MATERIAL AND METHODS. In the acute period of ischemic stroke (1–21 days), 92 patients with symptomatic stenosis of the internal carotid artery of 50% or more were operated on using carotid endarterectomy . There were 66 men and 26 women. The average age was 65.7±8.4 years. All patients were divided into three groups depending on the timing of the operation: Group 1, where the operation was performed on the 1st week of stroke (n=48); Group 2, where the operation was performed on the 2nd week after stroke (n=28); Group 3, where carotid endarterectomy was performed on the 3rd week after stroke (n=16). In-hospital endpoints of the study in each group were ipsilateral ischemic stroke, any other stroke (contralateral ischemic or hemorrhagic), myocardial infarction, wound hemorrhagic complications requiring repeated operation and surgical hemostasis, death, and major adverse cardiovascular events (stroke + myocardial infarction + fatal outcome).RESULTS. There were no postoperative ipsilateral ischemic strokes, myocardial infarctions, or deaths in the study group (92 patients). In the overall group of patients (n = 92), the incidence of any postoperative stroke was 2.2% (2 patients): one hemorrhagic stroke on the side of carotid endarterectomy (group 3) and one contralateral ischemic stroke on the first postoperative day in a patient with bilateral critical stenosis of the internal carotid artery (group 1). Postoperative wound hematoma, which required revision and bleeding arrest in the early postoperative period, developed in one (1.1%) patient in Group 1. The overall incidence of major adverse cardiovascular events was 2.2% or 2 patients. In all three groups, a statistically significant and positive effect in regression of the initial neurological deficit was obtained at discharge. In patients operated in the first week after stroke, the neurological deficit at discharge according to the National Institutes of Health Stroke Scale (NIHSS) and the modified Rankin scale was the lowest. In general, 31.3%, 17.9% and 12.5% of patients in groups 1, 2 and 3 were discharged without neurological deficit (0 points according to the NIHSS scale), respectively.CONCLUSIONS. Carotid endarterectomy performed in the acute period of ischemic stroke is a safe surgical intervention in the prevention of recurrent ipsilateral ischemic events. The most positive neurological dynamics and the least neurological deficit at discharge were achieved after operations performed in the first week of ischemic stroke.